2011
DOI: 10.1177/1741826711409325
|View full text |Cite
|
Sign up to set email alerts
|

Long-term beta blockers for stable angina: systematic review and meta-analysis

Abstract: Beta blockers may decrease the death and unstable angina when compared with no treatment, but no more effective than other anti-anginal agents on prophylaxis of myocardial ischaemia in stable angina patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…Therefore, improvement in quality of life is an important goal and a measure of therapeutic success in these patients. Despite this, there are few studies regarding improvements in quality of life on antianginal therapy (including beta-blocker) and the results are generally inconsistent [25][26][27][28].…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, improvement in quality of life is an important goal and a measure of therapeutic success in these patients. Despite this, there are few studies regarding improvements in quality of life on antianginal therapy (including beta-blocker) and the results are generally inconsistent [25][26][27][28].…”
Section: Introductionmentioning
confidence: 94%
“…Studies by Dargie et al and Rehnqvist et al demonstrated no mortality benefit with either BB, CA or the combination of both [39, 40]. Furthermore, in a meta-analysis by Shu et al, BBs did not reduce the risk of death or acute myocardial infarction in patients with stable ischemic heart disease [41]. A large longitudinal, observational analysis of 44,708 patients divided into three cohorts, those with known prior myocardial infarction, those with known coronary artery disease without myocardial infarction, and those with coronary artery disease risk factors only, found that the use of BBs was not associated with a lower risk of cardiovascular death, nonfatal MI, or nonfatal stroke.…”
Section: Management Of Anginamentioning
confidence: 99%
“…A systematic review and meta-analysis of randomised trials with nitrates for stable angina pectoris suggested that long-term administration of nitrates is beneficial for angina prophylaxis and improves exercise performance but might be ineffective for improving quality of life 6. Another systematic review and meta-analysis of randomised controlled trials (RCTs) on long-term BBs for stable angina pectoris suggested that BBs may decrease the rates of death and unstable angina when compared with no treatment but are no more effective than other antianginal agents on prophylaxis of myocardial ischaemia 7. Meta-analysis of randomised trials of BBs for stable angina suggested that BBs do not have statistically significant impact on mortality versus placebo or versus other active comparators 8.…”
Section: Introductionmentioning
confidence: 99%